Sie sind auf Seite 1von 32

# Fully Worked Solutions

cHAPTER 8 differentiation

Focus on Exam 8
1 (a) Let y = (x2 + 3)e-2x
dy

= (x2 + 3)(-2e-2x) + e-2x(2x)
dx

= 2e-2x(-x2 - 3 + x)
(b) Let u = x and y = sin3 x
1

y = sin3 u

= x 2

dy
du 1 - 12
= x
= 3sin2 u(-cos u)
dx 2
du
1

= -3sin2 u cos u
=
2 x
dy dy du
Hence,
=

dx du dx
1
= -3 sin2 u cos u
2 x
-3 sin2 x cos x
=
2 x

## 2 (a) Let y = ln (x3e-3x)

dy x (-3e ) + e (3x )

=
dx
x3e-3x
e-3x3x2(-x + 1)
=

x3e-3x
Copy back x3e-3x.
3(-x + 1)
=

x
3

-3x

-3x

d 3 -3x
(x e )
dx

(b) Let u = 5x

log5 u = x
ln u

=x
ln 5

ln u = x ln 5
1 du
= ln 5

u dx
du = u ln 5

dx
Oxford Fajar Sdn. Bhd. (008974-T) 2014

## ACE AHEAD Mathematics (T) Second Term

du
= 5x ln 5
dx

d x
(5 ) = 5x ln 5
dx
5x
Let y =
1 + 5x2
dy (1 + 5x2)(5x ln 5) - (5x)(10x)
=

dx
(1 + 5x2)2
5x[ln 5(1 + 5x2) - 10x]

=
(1 + 5x2)2
3 f(x) = e-2x sin 2x
f(x) = e-2x(2 cos 2x) + sin 2x(-2e-2x)

## = 2e-2xcos 2x - 2 sin 2xe-2x

f(x) = 2e-2x- 2 sin 2x + cos 2x(-4e-2x) - 2 sin 2x(-2e-2x) + e-2x(-4 cos 2x)

= -8e-2xcos 2x

## When x = , f(x) = -8e 3 cos

6
3

-
1

= -8e 3
2

= -4e

x+1
2x - 3
x+1
y = ln
2x - 3
= ln (x + 1) - ln (2x - 3)
4 e y =

dy
1
2
=
dx x + 1 2x - 3
At the x-axis, y = 0.
x+1

e0 =
2x - 3
x+1

1=
2x - 3
2x - 3 = x + 1

x=4

1
2
4 + 1 2(4) - 3
1
= -
5

## Hence, the equation of the tangent at the point (4, 0) is

1

y - 0 = - (x - 4)
5

5y = -x + 4
Oxford Fajar Sdn. Bhd. (008974-T) 2014

## Fully Worked Solutions

5 x2 - xy + y 2 = 7
When x = 3, 32 -3y + y2 = 7

y2 - 3y + 2 = 0

(y - 1)(y - 2) = 0

y = 1 or 2
2

x - xy + y2 = 7
Differentiating implicitly with respect to x,
dy
dy
2x - x + y(-1) + 2y = 0
dx
dx
dy

(-x + 2y) = -2x + y
dx
dy y - 2x

=
dx 2y - x

1 - 2(3)
= 5.
2(1) - 3
2 - 2(3)
The gradient of the tangent at the point (3, 2) is
= -4.
2(2) - 3
The gradient of the tangent at the point (3, 1) is

6 2y = ln (xy)
dy
dy x dx + y(1)

2 =
xy
dx
dy
dy
2xy = x + y
dx
dx
dy

(2xy - x) = y
dx
dy
y

=
dx 2xy - x
dy
1
=
At the point P(e2, 1),
dx 2(e2)(1) - e2
1

= 2
e
1
.
e2

Hence, the equation of the tangent at the point P(e2, 1) is
1

y - 1 = 2 (x - e2)
e
e2y - e2 = x - e2
e2y = x
Therefore, the gradient of the tangent is

7 x = e 4t = e2 t
1 2t
dx
= 2
e
dt
2 t

1 2

dx e2 t
=
dt
t
Oxford Fajar Sdn. Bhd. (008974-T) 2014

## ACE AHEAD Mathematics (T) Second Term

y = e6t

y = (e6t)2
y = e3t
dy
= 3e3t
dt
x = e2 t
ln x = 2 t

(ln x)2 = 4t
1
t = (ln x)2
4
dy
dy dt
=
dx dx
dt
3e3t
= 2 t
e
t
3e3t t

e2 t

4
1
= 3 ln x e
x
2

)1

3 (ln x)2

2
(ln x)

e3t = e4
3

= 3e 4 ln x
2x

(ln x)2

t = 1 ln x
2

8 x = e2t - 2
dx
= 2e2t

dt

y = et + t
dy

= et + 1
dt
dy
dy dt
=

dx dx
dt
et + 1

=
2e2t
When t = ln 2, x = e2ln 2 - 2
2

= eln 2 - 2

= 22 - 2
aloga x = x

=2
When t = ln 2, y = eln 2 + ln 2

= 2 + ln 2
Oxford Fajar Sdn. Bhd. (008974-T) 2014

e2

=x

## Fully Worked Solutions

dy eln 2 + 1
=
dx
2e 2ln 2
2+1

=
2(2)2
3

=
8
Hence, the equation of the tangent at the point where t = ln 2 is
3

y - (2 + ln 2) = (x - 2)
8
8y - 16 - 8 ln 2 = 3x - 6
8y = 3x + 10 + 8 ln 2
When t = ln 2,

9 x = -cos2 2
dx
= -2 cos 2(-2 sin 2)
d

= 4 cos 2 sin 2

y = sin2 2

dy
= 2 sin 2(2 cos 2)
d

= 4 sin 2 cos 2

dy
dy d

=
dx dx
d
4 sin 2 cos 2

=
4 cos 2 sin 2

=1
The gradient of the tangent is 1. Hence, the gradient of the normal is -1.

When = , x = -cos2
8
4
1 2

= -
2
1

=2

y = sin2
4
2
1

=
2
1

=
2
Hence, the equation of the normal is

1
1

y - = -1 x - -
2
2
1
1
y - = -x 2
2

y = -x

## ACE AHEAD Mathematics (T) Second Term

10 y = e2x - 6x + 7

= (e2x - 6x + 7)2
1
-
dy 1
= (e2x - 6x + 7) 2 (2e2x - 6)
dx 2
2e2x - 6

=
2 e2x - 6x + 7
2e2x - 6
=
2y
e2x - 3
=
y
dy
2x

y = e - 3
dx
d2y dy dy
= 2e2x

y 2 +
dx
dx dx
d2y
dy 2
y 2 +
= 2e2x[Shown]
dx
dx
11 y = e x ln x
1
dy
= ex + ln x e x
x
dx
dy
1
= e x + y
dx
x
dy
x = ex + xy
dx
dy
d 2y dy

x 2 + (1) = ex + x + y(1)
dx
dx
dx

12
12

dy
d 2y

x 2 + (1 - x) - y = e x
dx
dx

From ,
dy
e x = x - xy
dx

dy
dy
d 2y

x 2 + (1 - x) - y = x - xy
dx
dx
dx
dy
d 2y

x 2 + (1 - 2x) + (x - 1)y = 0[Shown]
dx
dx
cos x
12
y=
x

xy = cos x
dy

x + y(1) = -sin x
dx
dy

x + y = -sin x
dx
d 2y dy
dy
= -cos x

x 2 + (1) +
dx
dx
dx
dy
d 2y
x
+ 2 = -xy
2
dx
dx
dy
d 2y

x 2 + 2 + xy = 0[Shown]
dx
dx
Oxford Fajar Sdn. Bhd. (008974-T) 2014

## Fully Worked Solutions

13 y = cos x
1

= cos2 x
1
dy 1
= (cos x) 2 (-sin x)
dx 2
-sin x
=
2 cos x
= -sin x
2y
dy

2y = -sin x
dx
2
d y dy dy

2y 2 +
2
= -cos x
dx
dx dx

1 2

dy
d 2y

2y 2 + 2
dx
dx

1 2

+ cos x = 0

dy
d 2y
2y 2 + 2
dx
dx

1 2

+ y2 = 0[Shown]

14 y = e-2x sin x
dy
= e-2x cos x - 2 sin x e-2x
dx
dy
e-2x sin x = y
= e-2x cos x - 2y
dx
d2y
dy

= -e-2x sin x - 2 cos x e-2x - 2
dx2
dx

dy

+ 2y
cos x e-2x =
d2y
dy
dy
dx

+
2y

=
-y
2
2
2
dx
dx
dx

e-2x sin x = y

dy
d 2y
+ 4 + 5y = 0[Shown]
2
dx
dx

15 y = ln (1 - cos x)
dy
sin x

=
dx 1 - cos x
d 2y (1 - cos x)(cos x) - sin x sin x

=
(1 - cos x)2
dx2
cos x - cos2 x - sin2 x
(1 - cos x)2
cos x - (cos2 x + sin2 x)
=
(1 - cos x)2
=

cos x - 1
(1 - cos x)2

= -

1 - cos x
(1 - cos x)2
Oxford Fajar Sdn. Bhd. (008974-T) 2014

## ACE AHEAD Mathematics (T) Second Term

-1
1 - cos x

1
cos x - 1
1
1 dy
.
=
cos x - 1
sin x dx
d2y
1 dy
2=
sin x dx
dx
dy
d2y
sin x 2 = dx
dx
2
d y dy
= 0[Shown]
sin x 2 +
dx
dx

But from ,

1 2

1 2

16 y = esin x
dy
= cos xesin x

dx
dy
= y cos x

dx

esin x = y

1 2

d2y
dy
= y(-sin x) + cos x
dx2
dx

d2y
dy
2 = -ysin x + cos x
dx
dx

1 2

d2y
1 dy dy

= -y sin x +
y dx dx
dx2

d2y
1 dy
= -y sin x +
y dx
dx2

1 2

1 dy
cos x =
y dx

1 2

d2y
dy 2
y 2 = -y 2 sin x +
dx
dx
2
dy
dy 2
y 2 = -y2 ln y +
dx
dx

1 2
1 2

dy
d 2y
y 2 + y 2 ln y dx
dx

1 2

17

sin x = ln y

= 0[Shown]

y = ln (sin x + cos x)
dy cos x - sin x
=
dx sin x + cos x

dy 2
cos x - sin x 2
+1
+ 1 =
sin x + cos x
dx

1 2

(sin x + cos x)2

(sin x + cos x)2

## cos2 x + sin2 x + sin2 x + cos2 x

(sin x + cos x)2
1+1
sin2 x + cos2 x = 1

=
2
(sin x + cos x)
2

=
[Shown]
(sin x + cos x)2
d2y (sin x + cos x)(-sin x - cos x) - (cos x - sin x)(cos x - sin x)

=
(sin x + cos x)2
dx2
-sin2 x - 2 sin x cos x - cos2 x - (cos2 x - 2 sin x cos x + sin2 x)

=
(sin x + cos x)2
=

-2 sin2 x - 2 cos2 x
(sin x + cos x)2

-2(sin2 x + cos2 x)
(sin x + cos x)2

-2(1)
(sin x + cos x)2

= -

31 2 4
dy 2
+1
dx

dy
d2y
+
dx
dx2

1 2

+ 1 = 0[Shown]

x2
(x + 3)(x - 1)
x2
= 2
x + 2x - 3

18 (a) y =

## As y , the denominator of

x2
0
(x + 3)(x - 1)

(x + 3)(x - 1) 0

x -3 or 1
Therefore, x = -3 and x = 1 are vertical asymptotes.

1x

lim y = lim

x2
+ 2x - 3

x2
2
= lim 2 x
x
x + 2x - 3
x2 x2 x2

= lim

=1

1
2
1 + - 32
x x

1
1+0+0

## Therefore, y = 1 is the horizontal asymptote.

Oxford Fajar Sdn. Bhd. (008974-T) 2014

10

(b) y =

x2
x + 2x - 3
2

=
(x2 + 2x - 3)2
dx

(x2 + 2x - 3)2

2x2 - 6x
(x + 2x - 3)2
2

2 =
(x2 + 2x - 3)4
dx
=

## 2(x2 + 2x - 3)[(x2 + 2x - 3)(2x - 3) - (2x2 - 6x)(2x + 2)]

(x2 + 2x - 3)4
2[(x2 + 2x - 3)(2x - 3) - (2x2 - 6x)(2x + 2)]
(x2 + 2x - 3)3

When

dy
2x2 - 6x
= 0, 2
=0
(x + 2x - 3)2
dx
2x2 - 6x = 0
2x(x - 3) = 0
x = 0 or 3

When x = 0, y = 0 and

d2y 2[(-3)(-3) - 0]
=
(-3)3
dx2
2
= - (< 0)
3

When x = 3, y =

9
6(2)
3
4

2 =
(32 + 2 3 - 3)3
dx
= 6(> 0)

## 1 342 is a turning point and it is a local minimum point.

Therefore, 3,

(c) When y = 0, x = 0.

x2
(x + 3)(x - 1)
x2
is as shown.
x + 2x - 3
2

## Fully Worked Solutions

3 , 43

1
x- 3
x = 3 is the vertical asymptote.
1
(b) When x = 0, y = 4(-3)2 (-3)
1

= 36
3
19 (a) y = 4(x - 3)2 -

1
Thus, the graph cuts the y-axis at 0, 36 .
3
1
2
=0
When y = 0, 4(x - 3) x- 3
1

4(x - 3)2 =
x- 3

(x - 3)3 =

1
4

x-3=

1
1

43
1

x=

4
x = 3.63

1
3

+3

## Thus, the graph cuts the x-axis at (3.63, 0).

1
(c) y = 4(x - 3)2 x- 3

= 4(x - 3)2 - (x - 3)-1
dy
 = 8(x - 3)1(1) + (x - 3)-2(1)
dx
1
= 8(x - 3) +
(x - 3)2
2
dy

= 8 - 2(x - 3)-3(1)
dx2
2

=8(x - 3)3
Oxford Fajar Sdn. Bhd. (008974-T) 2014

11

12

dy
= 0,
dx
1
8(x - 3) +
=0
(x - 3)2
When

1
8(x - 3) = -
(x - 3)2
1
(x - 3)3 = 8
1
x - 3 = -
2

x = 2.5

1
When x = 2 ,
2
2
1
5
y=4 -3 2
5
-3
2
=1+2
=3
2
dy
2
=83
dx2
5
-3
2
= 8 - (-16)
= 24(> 0)

(d) When

8-

dy
= 0,
dx2
2

2
=0
(x - 3)3
2
=8
(x - 3)3
1
(x - 3)3 =
4
1
x= 1+3
43
x = 3.63

## From (b), when x = 3.63, y = 0.

d3y

= 6(x - 3)-4(1)
dx3
6

=
(x - 3)4
d3y
6
When x = 3.63, 3 =
dx (3.63 - 3)4

= 38.1 (i.e. 0)
Hence, (3.63, 0) is a point of inflexion.

## (e) The graph of y = 4(x - 3)2 -

1
is as shown below.
x-3
y

36

1
3

2.5 , 3
O

3.63

## 20 (a) The x-axis is the axis of symmetry.

(b) y2 = x2(4 - x)
y 2 0
x2(4 - x) 0
Since x2 0, x2(4 - x) 0 only if 4 - x 0 i.e. x 4.
Hence, the set of values of x where the graph does not exist is {x : x > 4}.
(c) y 2 = x2(4 - x)

= 4x2 - x3
dy
2y = 8x - 3x2
dx
dy 8x - 3x2
=

2y
dx
dy
8x - 3x2
=

dx 2(x 4 - x )
x(8 - 3x)
dy
=

dx 2x 4 - x
dy
8 - 3x
=

dx 2 4 - x

dy
When = 0,
dx
8 - 3x
=0
2 4 - x
8 - 3x = 0
8
x=
3
Oxford Fajar Sdn. Bhd. (008974-T) 2014

13

14

## ACE AHEAD Mathematics (T) Second Term

8
8
8
When x = , y = 4 3
3
3
= 3.08

2
2
Hence, 2 , 3.08 and 2 , -3.08 are turning points (whose tangents are horizontal).
3
3
dy
When
= ,
dx

2 4-x =0

x=4
When x = 4, y = 4 4 - 4

=0
Hence, (4, 0) is also a turning point where tangent is vertical.
(d) The graph of y2 = x2(4 - x) is as shown below.
y

2 32 , 3.08
O

2 32 , 3.08
1 - e2x
1 + e2x
(1 + e2x)(-2e2x) - (1 - e2x)(2e2x)
=
(1 + e2x)2
-2e2x[1 + e2x + (1 - e2x)]
=
(1 + e2x)2
-4e2x
=
(1 + e2x)2

21 (a) y =

dy
dx
dy
dx
dy
dx

## Since e2x > 0 and (1 + e2x)2 > 0, thus

1 - e2x
1 + e2x
y + ye2x = 1- e2x
e2x(1 + y) = 1 - y
1-y
e2x =
1+y

(b)

dy
-4e2x
=
< 0[Shown]
dx (1 + e2x)2

y=

11 -+ yy
1-y
1
x = ln
[Shown]
2
1 + y

2x = ln

## Fully Worked Solutions

dy
-4e2x
=
dx (1 + e2x)2

12 ln11 -+ yy

-4e

1-y

11 + y2

-4

1-y
1+
1+y

aloga x = x

1-y

11 + y2

-4

1-y 2

1 + e22ln 1 + y

1+y+1-y
1+y

-4

1-y

11 + y2

= -(1 - y)(1 + y)

= y2 - 1[Shown]

4
(1 + y)2

d2y
dy
= 2y
dx2
dx

Since

(c) lim
x

dy
d2y
d2y
< 0, 2 < 0 if y > 0 and 2 > 0 if y < 0.[Shown]
dx
dx
dx

(d) When y = 0,

1 - e2x
=0
1 + e2x

1 - e2x = 0
e2x = 1
2x = ln 1
2x = 0
x=0

1 - e2x
1 - e2x
=
-1
and
=1
lim
x- 1 + e2x
1 + e2x

y
1

## Thus, (0, 0) is a point of inflexion.

1 - e2x
is as shown beside.
Hence, the graph of y =
1 + e2x

15

16

22 (a)
A

6 cm

B
Q

k cm P
x cm
D

(2k + 6) cm

## CQR and CBS are similar triangles.

B

k cm

Q
x cm

R
[(2k + 6) 6] cm

Thus,

RC QR
=
SC BS

RC
x
=
(2k + 6) - 6 k

RC x
=
2k k

RC = 2x

Thus, DR = DC - RC
= 2k + 6 - 2x

(b) Area of PQRD,
L = DR QR
L = (2k + 6 - 2x)(x)
L = (2k + 6)x - 2x2[Shown]
(c) When L has a stationary value,

dL
=0
dx
2k + 6 - 4x = 0
4x = 2k + 6

x=

x=

2k + 6
4

2(k + 3)
4
k+3
x=
2

d 2L
= -4 (negative)
dx2

## Hence, the maximum value of L

2

k+3
k+3
-2
2
2

= (2k + 6)

= 2(k + 3)

k +2 3 - 2(k 4+ 3)

= (k + 3)2 -

(k + 3)2
2

(k + 3)2
2
MC
r
MC = r sin x
AC = 2MC
= 2r sin x

23 In OMC, sin x =

B
x
r cm
O
x x

rc

rc

OM
r
OM = r cos x

In DOMC, cos x =

Area of ABC,
1
AC BM
2
1
L = AC (BO + OM)
2
1
L = (2r sin x) (r + r cos x)
2
L = r2 sin x + r2 sin x cos x

L =

1
L = r2 sin x + r2(2 sin x cos x)
2
1
L = r2 sin x + r2 sin 2x
2
1
L = (2r2 sin x + r2 sin 2x)
2
r2
L = (2 sin x + sin 2x)[Shown]
2
dL r 2
= (2 cos x + 2 cos 2x)
dr 2
Oxford Fajar Sdn. Bhd. (008974-T) 2014

17

18

## When L has a stationary value,

dL

=0
dx
2
r
(2cos x + 2cos 2x) = 0
2

cos x + cos 2x = 0
cos x + 2 cos2 x - 1 = 0
2 cos2 x + cos x - 1 = 0
(2 cos x - 1)(cos x + 1) = 0
1

cos x = or cos x = -1
2
p
x = p (not accepted)

x=
3
d2L r 2
2 = (-2 sin x - 4 sin 2x)
2
dx
p
When x = ,
3
2
d L r2
p
2p
=
-2sin - 4sin

dx2 2
3
3

= -2.60r2 (< 0)

Hence, L is a maximum.
p
2p
r2
2sin + sin
3
3
2

r
= 2
2

Lmax =

3
3
+
2
2

3 3 2
r [Shown]
4
OR
24 In ORQ, cos a =
r

OR = r cos a

QM = MP

= OR

= r cos a
QR

In ORQ, sin a =
r

QR = r sin a
=

Therefore, the perimeter of ORQP,

y = OR + RQ + QM + MP + PO
y = r cos a + r sin a + r cos a + r cos a + r
y = r + r sin a + 3r cos a
y = r(1 + sin a + 3 cos a)[Shown]
dy
= r(cos a - 3sin a )
da

rc

m
a

P
r cm
a

## Fully Worked Solutions

When y has a stationary value,
dy
=0

dr

r(cosa - 3sina) = 0
cos a - 3sin a = 0

cos a = 3 sin a
1 sin a
=

3 cos a
1

tan a =
3
1

a = tan-1
3
d2y
2 = r(-sin a - 3 cos a)
da
d2y
Since sin a > 0 and cos a > 0, 2 < 0.
da
Thus, y is a maximum.

## ymax = r(1 + sin a + 3 cos a)

= r 11 +
=r 1+

3 10
10
+3
10
10

10

3
10

1
+3
10

a
3

sin a =

1
3
, cos a =
10
10

= (1 + 10 )r [Shown]

dV Change in volume
=
dt
Change in time
1 3
- 13

= 2
24
7
m3 hour-1

= -
192
(b) V = x3
dV

= 3x2
dx
1
dx

=
dV 3x2
dx dx dV

=
dt dV dt
1
7

= 2 3x
192
7
1

=
3(0.7)2
192

= -0.0248 m hour-1

Rate of decrease = 0.0248 mh-1
25 (a)

19

20

26 AB = x2 + 32
1

= (x2 + 9)2
1
d(AB) 1 2

= (x + 9) 2 (2x)
2
dx
x

= 2
x +9
d(AB) d(AB) dx

=

dt
dx
dt
x

= 2
2
x +9
4

= 2
2
4 +9

= 1.6 units s-1
27 (a)
(x + 2 r ) cm
Q
x cm

(x + 2) cm
N

r cm

r cm
O

## RNO and RQP are similar triangles.

Thus, NO = NR
QP QR
r x+2-r

=
x
x+2

r(x + 2) = x(x + 2 - r)

rx + 2r = x2 + 2x - rx

2rx + 2r = x2 + 2x
r(2x + 2) = x2 + 2x
x2 + 2x

r=
[Shown]
2x + 2
x2 + 2x
(b) r =
2x + 2
dr (2x + 2)(2x + 2) - (x2 + 2x)(2)

=
dx
(2x + 2)2
dr 4x2 + 8x + 4 - 2x2 - 4x

=
dx
(2x + 2)2
dr 2x2 + 4x + 4

=
dx
(2x + 2)2
dr 2(x2 + 2x + 2)

=
[2(x + 1)]2
dx

dr x2 + 2x + 2
=
dx
2(x + 1)2

## Fully Worked Solutions

dx dx dr
=

dt dr dt

2(x + 1)2
(-0.4)
x2 + 2x + 2

2(4 + 1)2
(-0.4)
42 + 2(4) + 2

50
-0.4
26

= -0.769 cm s-1

28 y = xe x+1
dy
= xe x+1 + ex+1
dx
= e x + 1(x + 1)
dy
x
dx
= e x+1(x + 1)dx x changes from 1 to 1.01. So, dx = 1.01 - 1.

ynew = yoriginal + y

## 1.01e2.01 = 1(e1+1) + [e1+1(1 + 1)](1.01 - 1)]

The value of y
when x = 1.01.

The value of
y when x = 1.

dy
The value of
dx
when x = 1.

1.01e2.01 = e2 + 2e2(0.01)
7.3891 + 2(7.3891)(0.01)
e2.01 =
1.01
2.01

e = 7.46
29

cos x
x
xy = cos x
y=

dy
x+ y(1) = -sin x
dx

dy
x + y = -sin x
dx
2
d y dy
dy
= -cos x

x 2 + (1) +
dx dx
dx
d2y
dy
x 2 + 2 = -xy
dx
dx
2
dy
dy

x 2 + 2 + xy = 0[Shown]
dx
dx

21

22

## ACE AHEAD Mathematics (T) Second Term

30 y = x ln (x + 1)
dy
1
+ ln (x + 1)(1)
= x
x+1
dx
x
=
+ ln (x + 1)
x+1
dy
x
y =

dx

( x +x 1 + ln (x + 1)) x

ynew = yoriginal + y

1.01 ln (1.01 + 1) = 1 ln (1 + 1) +
The value of y
when x = 1.01.

The value of y
when x = 1.

## x changes from 1 to 1.01. So, dx = 1.01 - 1.

1 +1 1 + ln (1 + 1) (1.01 - 1)
dy
The value of
dx
when x = 1.

## 1.01(ln 2.01) = 0.70508

ln 2.01 = 0.698
4ekt - 1
31 (a) f(t) = kt
4e + 1
4e0 - 1
f(0) = 0
4e + 1
3

=
5
(4ekt + 1)(4kekt) - (4ekt - 1)(4kekt)

(b) f(t) =
(4ekt + 1)2
2kt
(16ke + 4kekt - 16ke2kt + 4kekt)
f(t) =
(4ekt + 1)2
8kekt
f(t) =
(4ekt + 1)2
Since k is a positive integer, f(t) > 0.

## (c) LHS = k{1 - [f (t)]2}

4}
2

4ekt - 1
4ekt + 1
(4ekt + 1)2 - (4ekt - 1)2
= k
(4ekt + 1)2
2kt
16e + 8ekt+ 1 - (16e2kt- 8ekt+ 1)
= k
(4ekt + 1)2
16kekt
=
(4ekt + 1)2
8kekt
=2
(4ekt + 1)2
= 2f (t)
= RHS
= k 1 -

{
{

23

## Fully Worked Solutions

k{1 - [f(t)]2} = 2f (t)

k - k[f(t)]2 = 2f (t)
-2k[f(t)] f (t) = 2f (t)

-k[f(t)] f (t) = f (t)

f (t) = -k[f(t)] f (t)
Since k and f (t) are both positive, f (t) < 0.
4ekt - 1
t 4ekt + 1
4ekt 1
- kt
kt
= lim e kt e
t
1
4e
+
ekt ekt
1
4 - kt
e
= lim
t
1
4 + kt
e
4-0
=
4+0
=1

## (d) lim f (t) = lim

t

1
1

1
4 - kt
kt
e
4e
1
(e) lim
= lim
t 4ekt + 1
t
1
4 + kt
e

=4-0
4+0

=1
4(1) - 1 3
When t = 0, f(0) =
=
4(1) + 1 5


Therefore, the graph of f(t) intersects the
3
f(t)-axis at the point 0, .
5
kt
When f(t) = 0, 4e - 1 = 0
4ekt + 1

4ekt - 1 = 0
1

ekt =
4
1

kt = ln
4
1 1

t = ln
k 4

f(t )
1

1
1 ln

k
4

3
5

f(t ) =

4ekt 1
4ekt + 1
1

Key Point:
If f(t) = -k[f(t)]f(t), since k > 0 and f(t) > 0, f (t) > 0 only when f(t) = 0. Therefore, the point of
1 1
ln , 0 .
inflexion is on the t-axis, i.e.
k 4

24

## ACE AHEAD Mathematics (T) Second Term

x
1 + x2
(1 + x2)(1) - x(2x)
=
(1 + x2)2
1 - x2
=
(1 + x2)2

32 y =
dy

dx
dy

dx

dy 1 - x2
=
x 2
dx
y

dy (1 - x2) y2
=
x2
dx
dy

x2 = (1 - x2) y2[Shown]
dx
33
y = sin x - cos x
sin x + cos x

(sin x + cos x)y = sin x - cos x
dy
(sin x + cos x) + y(cos x - sin x) = cos x + sin x
dx
dy

(sin x + cos x)

dy

(sin x + cos x)

sin x - cos x
=0
1dx -12 - y 1sin
x + cos x2
dy

dy

## 1dx -12 - y(y) = 0

dy
- 1 - y2 = 0
dx
d2y
dy
=0
- 2y
dx 2
dx

dy
d2y
[Shown]
2 = 2y
dx
dx

34 y =
dy
=
dx

x3
x2 - 1
(x2 - 1)(3x2) - x3(2x)
(x2 - 1)2
3x4 - 3x2 - 2x4
(x2 - 1)2
x4 - 3x2
(x2 - 1)2
x2(x2 - 3)
(x2 - 1)2

## d2y (x2 - 1)2(4x3 - 6x) - (x4 - 3x2)(2)(x2 - 1)1(2x)

=
(x2 - 1)4
dx2
(x2 - 1)2(2x)(2x2 - 3) - 4x(x4 - 3x2)(x2 - 1)
=
(x2 - 1)4
2x(x2-1)[(x2-1)(2x2-3) - 2(x4 - 3x2)]
=
(x2 - 1)4
2x[2x4 - 5x2 + 3 - 2x4 + 6x2]
=
(x2 - 1)3
2x(x2 + 3)
= 2
(x - 1)3
d3y (x2 - 1)3(6x2 + 6) - (2x3 + 6x)(3)(x2 - 1)2(2x)

=
(x2 - 1)6
dx3
2
3 2
6(x - 1) (x + 1) - 6x(2x3 + 6x)(x2 - 1)2
=
(x2 - 1)6
2
2
2
6(x - 1) [(x - 1)(x2 + 1) - x(2x3 + 6x)]
=
(x2 - 1)6
6(x4 - 1 - 2x4 - 6x2)
=
(x2 - 1)4
6(-x4 - 6x2 - 1)
=
(x2 - 1)4
dy
=0
When
dx
x2(x2 - 3) = 0

x = 0 or 3
When x = 0, y = 0 and

When x = 0,

d2y 2(0)(02+ 3)
=
(02 - 1)3
dx2
=0

## d3y 6(-04 - 6(0)2 - 1)

=
(02 - 1)4
dx3

= -6
d3y
Since 3 0, then (0, 0) is a point of reflextion.
dx

3)
3-1
3 3
=
2

When x = 3, y =

and

Since

d2y 2 3(3 + 3)
=
(3 - 1)3
dx2
3
= 3
2
d2y
> 0, then
dx 2

3
3, 3 is a minimum point.
2
Oxford Fajar Sdn. Bhd. (008974-T) 2014

25

26

## ACE AHEAD Mathematics (T) Second Term

and

(-

3)
3-1
3 3
= -
2

When x = - 3, y =

## d2y 2(- 3 )(3 + 3)

=
(3 - 1)3
dx2
3
= - 3.
2

d2y
3
2 < 0, then - 3, - 3 is a maximum point.
2
dx
x3
is 0, x2 - 1 = 0 x = 1
When the denominator of y = 2
x -1

Since

## Hence, x = -1 and x = 1 are asymptotes.

x3
is as shown below.
The graph of y = 2
x -1

3 ,

3 3
3 ,
2

3 3
2

x

x3 = k (x2 - 1)
x3
=k
2
x -1
By sketching the straight lines y = k on the above graph and as k varies, we obtain the
following results.
Value of k
3
k> 3
2
3
k= 3
2
3
3
- 3<k< 3
2
2
3
k=- 3
2
3
k<- 3
2
Oxford Fajar Sdn. Bhd. (008974-T) 2014

3
2
1
2
3

## Fully Worked Solutions

x
x2 - 1
dy (x2 - 1)(1) - x(2x)
=
(x2 - 1)2
dx
-x2 - 1
= 2
(x - 1)2
-(x2 + 1)
= 2
(that is < 0)
(x - 1)2
35 y =

Since

dy
< 0 for all real values of x, then the gradient of the curve is always decreasing.
dx

## d2y -(x2 - 1)2(2x) + (x2 + 1)(2)(x2 - 1)(2x)

2 =
(x2 - 1)4
dx
-2x(x2 - 1)[x2 - 1 - 2(x2 + 1)]
=
(x2 - 1)4
-2x(-x2 - 3)
=
(x2 - 1)3
2x(x2 + 3)
= 2
(x - 1)3
d2y
= 0,
dx2
2x(x2 + 3)
2
=0
(x - 1)3

x=0
When

When x = 0, y =

0
02 - 1

=0

## d3y (x2 - 1)3(6x2 + 6) - (2x)(x2 + 3)(3)(x2 - 1)2(2x)

3 =
(x2 - 1)6
dx
6(x2-1)3(x2+1)-(12x2)(x2+3)(x2-1)2
(x2 - 1)6
2
2
2
6(x -1) [(x - 1)(x2 + 1)-(2x2)(x2 + 3)]
=
(x2 - 1)6
6(x2 - 1)2(x4 - 1 - 2x4 - 6x2)
=
(x2 - 1)6
6(-x4 - 1 - 6x2)
=
(x2 - 1)4
d3y 6[-04 - 1 - 6(0)2]
When x = 0, 3 =
(02 - 1)4
dx

= -6 (that is 0)
=

Since

d2y
d3y
0 when x = 0, then (0, 0) is the point of inflexion.
2 = 0 and
dx
dx3

27

28

## When the curve concaves upwards,

d2y

>0
dx2
2x(x2 + 3)

>0
(x2 - 1)3
2x(x2 + 3)

>0
[(x + 1)(x - 1)]3
2x(x2 + 3)

>0
(x + 1)3(x - 1)3
+

x >0

(x + 1)3 > 0

x2 + 3 > 0
(x 1)3 > 0

Hence, the intervals for which the curve is concave upwards are -1 < x < 0 or x > 1.
x
The curve y = 2
is as shown below.
x -1
y

2
36 (a) x = t -
t

y = 2t +

dx
2
= 1 + 2
dt
t
dy
dy dt
=

dx dx
dt
1
2- 2
t

=
2
1+ 2
t

dy
1
=2- 2
dt
t

2t2 - 1
t2 + 2

1
t

## Fully Worked Solutions

2
t 2 + 2 2t 2 - 1

2t 2 + 4
-5

dy
5
=2- 2
[Shown]

t +2
dx
dy

Let m =
dx
5

m=2- 2
t +2
5

(m - 2) = - 2
t +2

(m - 2)(t2 + 2) = -5
mt2 + 2m - 2t2 - 4 = -5

(m - 2)t2 = -1 - 2m
-1 - 2m

t2 =
m-2
1 + 2m

t2 =
2-m
t >0
1 + 2m
> 0
2-m

## The question states that t 0.

So, we write t 2 > 0 and not t2 0.

1 + 2m > 0

2m>0

1
2

x
+

1
1 dy
< 2[Shown]
Hence, - < m < 2, that is, - <
2
2 dx
dy 1
=
dx 3
5
1
=
2- 2
t +2 3
5
1
2- = 2
3 t +2
5
5
= 2
3 t +2
t2 + 2 = 3
t2 = 1
t = 1

(b)


When t = 1, x = 1

= -1

2
1

29

30

and

y = 2(1) +
=3

1
1

## When t = -1, x = (-1) =1

and

2
(-1)

y = 2(-1) +

1
(-1)

= -3

Hence, the coordinates of the required points are (-1, 3) and (1, -3).
37 x 2 sin q
y 3 cos q
dx
dy
2 cos q
3 sin q
dq
dq
dy
dy dq 3 sin q
=
=
dx dx 2 cos q
dq

3
= tan q
2
3
dy

When q = ,
= tan
4 dx
2
4
3
=
2
3
2
3
When q =

, x = 2 sin
4
4
1
= 2
2
= 2

When q

p
p
, y 3 cos
4
4
1
3
2

3 2
2

## Fully Worked Solutions

Equation of normal is

(
)
2 = 4( x - 2 )

3 2 2
y= x- 2
2
3
6y -9

6 y - 9 2 = 4x - 4 2
6 y = 4x + 5 2

x 2 + xy + y 2 = 4
dy
dy
2 x + x + y (1) + 2 y = 0
dx
dx
dy
( x + 2 y ) = 2x y
dx
dy 2 x y
=
dx x + 2 y
dy 2 x + y

[Shown]
+
=0
dx x + 2 y

38 (a)

(b) At x-axis, y = 0,
x2 + 0 + 0 = 4

x = 2

## \ (2, 0) and (2, 0)

-2 ( 2 ) + 0

2 + 2 ( 0)
= -= 2-2
2 ( 2 ) 0
2 + 2 ( 0 )
= -2
At y-axis, x = 0,

02 + 0(y) + y2 = 4

y = 2

## \ (0, 2) and (0, 2)

-2 ( 0 ) - 2

=-

1
2

0 + 2 ( 2)

= - 1
2
-2 ( 0 ) - ( -2 )
1
0 + 2 ( -2 )
2

= - 1
2

31

32

## (c) At stationary points,

dy
=0
dx

-2 x - y
=0
x + 2y
-2 x - y = 0
y = -2 x

Substituting y = 2x into x2 + xy + y2 = 4

x2 + x(2x) + 4x2 = 4
3x2 = 4
4
x2 =
3

x=

2
y = -2

4
=
3

2
3

2 -4
2 4
,
Stationary points are
,
and
.
3 3
3 3
y

(d)
2 , 4

3 3

2
2

2
2 , 4